PENGARUH MEDIA RODA PUTAR PELANGI TERHADAP KEAKTIFAN BELAJAR SISWA PADA MATA PELAJARAN PKN DI KELAS III MIN 7 KOTA MEDAN - Siti Rubiah Dalimunthe; Ramadhan Lubis; Eka Yusnaldi (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2024)
The learning process is not innovative, especially in terms of the use of media, and learning becomes monotonous and uninteresting if a conventional approach is used. This is the motivation of this research. This has an impact on students' low interest in learning, which in turn causes them not to have many learning activities. In this research, researchers used a quantitative approach, and the type of research used was quasi-experiment. This data is collected using questionnaires, tests and instructions. The purpose of this research is to find out how students who receive Rainbow Spinning Wheel training differ from students who do not receive such training.The results of the research show that the use of rainbow spinning wheel media significantly changes the learning abilities of students in class III MIN 7 Medan City. This is shown by the average learning activeness score of students who use the Rainbow Spinning Wheel media of 80. On the other hand, the t test results obtained, 20.6 versus 16.74, indicate that the average learning activeness of students who do not use the Roda media Rainbow Spin is 71.78.